La idea de la guerra: filigranas para su estudio (2011)
The present article obeys to the interest that exists in the general scope; to write on subjects related to the war and the conflict. In this case; one is not to repeat the reflections provoked on critical; sociological or political aspects: it is plus to philosophical or literary reflection; with a noticeable political emphasis. Like article; it is formed following a model of metaphorical anecdotal and writing; until attaining to give form to a filigree of the war.